Studi Literatur Kebijakan Implementasi Profil Pelajar Pancasila - Nur'im Septi Lestari; Syamsul Hadi; Shirly Rizki Kusumaningrum (Cetta: Jurnal Ilmu Pendidikan, 2023)
The incorrect interpretation implies a difference in understanding the essence of Pancasila among those involved in this project. If the implementation policy of the Pancasila student profile is inconsistent or unclear, it can lead to misconceptions among those responsible for executing it. The purpose of this research is to determine the implementation of the Pancasila policy profile. This study applies a qualitative descriptive method with a literature study approach as a source of research data, involving various types of documents such as books, articles, journals, and other documents relevant to the research topic. Data collection techniques are carried out through documentation by gathering supporting document sources. The research process involves steps of data collection, processing, and drawing conclusions using a literature study. The results of this research are that Pancasila, as the foundation of the Indonesian state, encompasses five principles involving values such as Belief in the One and Only God, Just and Civilized Humanity, Unity of Indonesia, Democracy Led by the Wisdom of Deliberations/Representatives, and Social Justice for All Indonesian People. Article 31 Paragraph 1 of the 1945 Constitution states that "every citizen has the right to receive an education," which is one of the goals of education in Indonesia. This concept is further explained in the fourth paragraph of the Preamble to the 1945 Constitution, which states the goal of "enlightening the life of the nation." The right to education is emphasized as a universal right without discrimination, considered as a means to achieve a dignified life and to humanize oneself. The results of this research include the integration of Pancasila subjects into the curriculum, character education in the Pancasila lesson profile, Pancasila teaching methods, Pancasila as a strengthening of national identity, the development of teaching materials for Pancasila lessons, and the involvement of parents and the community in building the nation's generation.